A CROSS-SECTIONAL STUDY OF THE CORRELATION BETWEEN DENGUE SEROLOGICAL MARKERS AND PLATELET COUNT IN THE NALGONDA REGION. - Balerao , Akhil Raj; Dara, Saranya; Sultana, Ayesha (Student's Journal of Health Research Africa, 2025)
Background: Dengue virus infection has emerged as a significant public health concern in recent decades. Early diagnosis is vital for reducing morbidity and mortality. Laboratory evaluations, including dengue serological markers and platelet counts, play a crucial role in diagnosis and predicting disease progression. This study aims to evaluate the utility of dengue-specific serological markers and explore their correlation with platelet counts in dengue-positive cases. Materials and Methods: A cross-sectional prospective study was conducted at a tertiary healthcare center in Nalgonda from December 2022 to May 2023. Clinically suspected dengue cases from outpatient, emergency, and inpatient departments were included. Dengue-specific serological markers (NS1, IgM) were tested via ELISA and correlated with platelet counts using the Chi-square test. Data analysis was performed using Epi Info and MS Excel. Results: Out of 2180 clinically suspected cases, 183 (8.39%) were dengue-positive. Among them, 112 (61.2%) were male and 71 (38.8%) were female. Thrombocytopenia (platelet count <100,000/mm³) was observed in 98 cases (53.5%). Thrombocytopenia was most prevalent among IgM-positive individuals (32.65%) and those positive for NS1 antigen alone (28.57%). A statistically significant association was observed between the presence of dengue serological markers and low platelet counts (p < 0.05), indicating a positive correlation between serological positivity and thrombocytopenia. Conclusion: Thrombocytopenia is a common finding in dengue-positive cases, especially during the early and acute phases of infection indicated by NS1 and IgM positivity. The correlation between serological markers and platelet count supports their combined use for early diagnosis and prognosis, potentially improving clinical outcomes. Recommendations: Routine use of NS1, IgM, and platelet count assessments is advised for timely diagnosis and disease monitoring in dengue-endemic regions.